Torque-generating units of the bacterial flagellar motor are rotary motors - Basarab G. Hosu; Alina M. Vrabioiu; Aravinthan D. T. Samuel (Proceedings of the National Academy of Sciences, 2025)
Escherichia coli swims using helical flagellar filaments driven at their base by a rotary motor. Torque-generating “stator” units drive the bacterial flagellar motor by transmitting mechanical power to a cytoplasmic “rotor,” the C-ring. Each stator unit is a proton-conducting heteromer. A central dimer of two MotB proteins anchors to the cell wall. A surrounding pentamer of five MotA proteins transmits mechanical power to the C-ring. This asymmetrical 5:2 structure is consistent with rotation as the mechanism of torque generation. Here, we test the hypothesis that the MotA 5 MotB 2 stator units are rotary motors themselves and interact with the rotor like intermeshed gearwheels, where rotation of the C-ring is directly coupled to MotA 5 rotation around the MotB 2 . We used in vivo polarized photobleaching microscopy. When a subset of fluorescent domains inside a multimer is rapidly photobleached by a strong pulse of polarized light, the induced polarization-dependent fluorescence of unbleached domains becomes a reporter of angular orientation. We applied polarized photobleaching microscopy to tethered cells rotating by single flagellar motors. We probed fluorescently labeled MotA pentamer and MotB dimer calibrated to motor rotation. The MotB dimer rotates at the same angular speed as the cell body, consistent with its anchor to the cell wall. The MotA pentamer rotates ∼ 6.2 × faster than the flagellar motor, revealing the gear ratio between stator and rotor.